Penyuluhan Pelatihan Dan Pendampingan Pengendalian Hama Dan Penyakit Tanaman Kakao Menggunakan Pestisida Nabati - Misdawati; Samsinar; Bande, La Ode Santiaji; Hamzah, Muhaimin; Abdullah, Weka Gusmiarty; Arimbawa, Putu; Hidayat, Ahid; Indrawati, Indrawati; Cholik, Saiful Nur; Sari, Mayang (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
Tunas Mekar Farmer Group in Tumbudadio Village, Tirawuta District, East Kolaka Regency. Located in the east, bordering Konawe Regency. Its location in the highlands (750 meters above sea level) has good potential for cultivating cocoa plantations. One of the obstacles often faced by farmer groups is the presence of plant pests (OPT). Until now, cocoa farmers usually use chemical pesticides that are sold on the market. Halu Oleo University Thematic KKN 2023 students provide another alternative to cocoa farmers, namely the use of plant-based pesticides that are more environmentally friendly, by providing training to the community regarding the manufacture of plant-based pesticides. The methods used are counseling, training and application. The result of this service is increased knowledge and skills about the benefits and methods of making botanical pesticides made from wild plants. Self-made vegetable pesticides can reduce production costs and have the potential to become a home industry.